Radio Programme on How to Improve Yields in Groundnuts - Mubiru, Wasswa (Technical Centre for Agricultural and Rural Cooperation, 2008)
Despite the high local demand for groundnuts, farmers? yields continue to dwindle, averaging 560kg/ha of dry seed. However, yields of over 1750kg/ha have been achieved in experimental plots, indicating a good potential to improve farmer?s yields. It is, therefore, possible to increase groundnut production if the farmers could improve or adopt improved production practices.